Age-sex specific pulmonary embolism-related mortality in the USA and Canada, 2000–18: an analysis of the WHO Mortality Database and of the CDC Multiple Cause of Death database. Issue 1 (January 2021) - Barco, Stefano; Valerio, Luca; Ageno, Walter; Cohen, Alexander T; Goldhaber, Samuel Z; Hunt, Beverley J; Iorio, Alfonso; Jimenez, David; Klok, Frederikus A; Kucher, Nils; Mahmoudpour, Seyed Hamidreza; Middeldorp, Saskia; et al.
Summary: Background: Pulmonary embolism (PE)-related mortality is decreasing in Europe. However, time trends in the USA and Canada remain uncertain because the most recent analyses of PE-related mortality were published in the early 2000s. Methods: For this retrospective epidemiological study, we accessed medically certified vital registration data from the WHO Mortality Database (USA and Canada, 2000–17) and the Multiple Cause of Death database produced by the Division of Vital Statistics of the US Centers for Disease Control and Prevention (CDC; US, 2000–18). We investigated contemporary time trends in PE-related mortality in the USA and Canada and the prevalence of conditions contributing to PE-related mortality reported on the death certificates. We also estimated PE-related mortality by age group and sex. A subgroup analysis by race was performed for the USA. Findings: In the USA, the age-standardised annual mortality rate (PE as the underlying cause) decreased from 6·0 deaths per 100 000 population (95% CI 5·9–6·1) in 2000 to 4·4 deaths per 100 000 population (4·3–4·5) in 2006. Thereafter, it continued to decrease to 4·1 deaths per 100 000 population (4·0–4·2) in women in 2017 and plateaued at 4·5 deaths per 100 000 population (4·4–4·7) in men in 2017. Among adults aged 25–64 years, it increased after 2006. The median age at death from PE decreased from 73 years to 68 years (2000–18). The prevalence of cancer, respiratory diseases, and infections as a contributing cause of PE-related death increased in all age categories from 2000 to 2018. The annual age-standardised PE-related mortality was consistently higher by up to 50% in Black individuals than in White individuals; these rates were approximately 50% higher in White individuals than in those of other races. In Canada, the annual age-standardised mortality rate from PE as the underlying cause of death decreased from 4·7 deaths per 100 000 population (4·4–5·0) in 2000 to 2·6 deaths per 100 000 population (2·4–2·8) in 2017; this decline slowed after 2006 across age groups and sexes. Interpretation: After 2006, the initially decreasing PE-related mortality rates in North America progressively reached a plateau in Canada, while a rebound increase was observed among young and middle-aged adults in the USA. These findings parallel recent upward trends in mortality from other cardiovascular diseases and might reflect increasing inequalities in the exposure to risk factors and access to health care. Funding: None.